THE ROLE OF THE PROMOTIONAL VIDEO "WONDERFUL INDONESIA: A VISUAL JOURNEY" ON BRAND IMAGE AND TOURIST VISITING INTEREST TO WAKATOBI - Santoso, Herien Natasya; Widyawati, Christy; Adityaji, Rizki (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2021)
Wakatobi is a tourist destination that has potentials for remarkable natural beauty. The Indonesian government is also aggressively promoting Wakatobi through the making of the video Wonderful Indonesia: A Visual Journey. However, the tourist visiting rate in Wakatobi is still not very high. Therefore, this study aims to determine the effect of the promotional video on brand image and interest in visiting Wakatobi. This study involved 151 people as samples and the results showed that promotional videos are able to have a positive and significant influence on brand image and tourist visiting interest. Likewise, the brand image is able to provide a positive and significant influence on tourist visiting interest